2014
DOI: 10.1371/journal.pone.0088337
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Gene Approach for Parasite Resistance in Sheep – Variation in Immune Pathway Genes and Association with Fecal Egg Count

Abstract: Sheep chromosome 3 (Oar3) has the largest number of QTLs reported to be significantly associated with resistance to gastro-intestinal nematodes. This study aimed to identify single nucleotide polymorphisms (SNPs) within candidate genes located in sheep chromosome 3 as well as genes involved in major immune pathways. A total of 41 SNPs were identified across 38 candidate genes in a panel of unrelated sheep and genotyped in 713 animals belonging to 22 breeds across Asia, Europe and South America. The variations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 49 publications
3
43
0
8
Order By: Relevance
“…Similar result was reported with the global F IS of 0.018 in the sheep population including Madras Red, Mecheri, and Pattanam sheep of Tamil Nadu [11] and the estimated mean F IS values across 19 short tandem repeat loci were found to be positive in wild Punjab Urial sheep and domestic sheep from West Asia breeds except Krainer Steinschaf and Madras Red which had F IS values of −0.005 and −0.001, respectively [14]. The global F IS observed in the present study is much lower than the previous reports in European sheep (0.123) [15], Nigerian sheep (0.335) [16], and Bulgarian sheep (0.288) [17].…”
Section: Discussionsupporting
confidence: 89%
“…Similar result was reported with the global F IS of 0.018 in the sheep population including Madras Red, Mecheri, and Pattanam sheep of Tamil Nadu [11] and the estimated mean F IS values across 19 short tandem repeat loci were found to be positive in wild Punjab Urial sheep and domestic sheep from West Asia breeds except Krainer Steinschaf and Madras Red which had F IS values of −0.005 and −0.001, respectively [14]. The global F IS observed in the present study is much lower than the previous reports in European sheep (0.123) [15], Nigerian sheep (0.335) [16], and Bulgarian sheep (0.288) [17].…”
Section: Discussionsupporting
confidence: 89%
“…These growth traits are affected by many factors, such as genotype, sex, age, breed, nutritional level, and other environmental factors (Gui et al, 2014). Accumulating evidence suggests that the candidate gene approach is one of many methods suitable for analysis of the association between gene polymorphism and phenotypes, which is a promising strategy for the genetic improvement of economically important quantitative traits (Edmunds et al, 2009;Periasamy et al, 2014). GH is a single-chain polypeptide hormone mainly secreted by somatotropes of the anterior pituitary gland and is an important regulator of somatic growth in almost all vertebrates Rak and Gregoraszczuk, 2008;Delgadin et al, 2015;Odle et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Among sheep breeds a considerable variation on their ability to resist GIN has been demonstrated (Periasamy et al, 2014). Similarly, a genetic variation even within the animals of the same breed has been reported for sheep populations of Merino, Romney, Scottish Blackface and Feral Soay sheep (Periasamy et al, 2014). Host resistance is a heritable feature with wide variability among individuals.…”
Section: The Role Of Cytokines and T Helper (Th) Cellsmentioning
confidence: 96%
“…The OAR-12 remains an interesting candidate, because of a 10-Mbp region affecting FEC both after the first and the second infection (Salle et al, 2012). Periasamy et al (2014) reported strong phylogeographic structure and balancing selection operating SNPs located within immune pathway genes. This study identified a total of 41 SNPs within 38 candidate genes, located in sheep chromosome 3, as well as in other genes involved in major immune pathways, in a panel of 713 unrelated sheep, belonging to 22 breeds across Asia, Europe and South America.…”
Section: The Role Of Nutritionmentioning
confidence: 99%
See 1 more Smart Citation